The Relationship Between Eating Behavior And Nutritional Status Of Cross-Track 1 Midwifery Students Of Universitas ‘Aisyiyah Yogyakarta - Yulianti Uswatun Hasanah; Rohmah, Fayakun Nur (Sahabat Publikasi Kuu, 2024)
Background: Nutritional problems (underweight, overweight, or obesity) in adolescents will cause a decrease in intelligence, learning ability, endurance, work productivity, and fitness and carry long-term ongoing risks. A person’s nutritional status is influenced by many factors, one of which is eating behavior. Eating behavior is one’s action and behavior when responding to or reacting to stimuli to food that is influenced by attitudes, knowledge, feelings, and food perceptions. Objective: The study aims to determine the relationship between eating behavior and the nutritional status of cross-track 1 midwifery students at Universitas ‘Aisyiyah Yogyakarta. Method: The study is descriptive research with a cross-sectional approach. The population consisted of 48 respondents. The sampling technique was total sampling. The bivariate analysis technique used the Kendall-Tau test. The research instruments included the Dutch Eating Behavior Questionnaire (DEBQ) which had been modified and adapted from Arif (2021) to measure eating behavior, body weight, height, and BMI to determine nutritional status. Results: There was a relationship between eating behavior and nutritional status of female cross-tract midwifery students of Universitas ‘Aisyiyah Yogyakarta. The results showed a p-value of 0.029 < 0.05 and a relationship coefficient value of 0.297 which indicated a low closeness of the relationship. Counclusion: Female students are recommended to increase their awareness, implement good eating behavior, and develop exercise habits to maintain normal nutritional status.